Transformation of Indigenous Traditions into Islamic Culture: An Examination of Sompa and Mahr in Pau-Paunna Sitti Rabiyatul Awaliya Manuscript - Mustari Mustari; Jarot Wahyudi; Habib Habib (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The current paper is dedicated to examining the traditional and Islamic dowry (sompa plus panai and mahr) in modern Bugis society. Nowadays, it is interesting to discuss the dowry as perceived by modern Bugis society as an expensive obligation. It is also relevant to investigate the dowry and how it is negotiated in Bugis society. For the researchers to find the answers, reading the classical Islamic text of Pau-Paunna Sitti Rabiyatul Awaliya was applied in the research as well as observing the Bugis society. Finally, the researchers found that the dowry (Sompa) in Bugis tradition has been regarded as an expensive payment and therefore needs to be negotiated accordingly. It is found in the classical text entitled Pau-Paunna Sitti Rabiyatul Awaliya (PPSRA) that Sitti gave her sompa free and changed the sompa to mahr in the form of mastery of knowledge. However, most of the Bugis women could not understand the implied message, so they still adhered to the sompa plus panai’ tradition. The implication of the study is to provide a reference by dowry fighters so that Bugis women are brave to move from sompa tradition to mahr without panai’.